The queerness of Native American literature - Tatonetti, Lisa (University of Minnesota Press, 2014)
A comprehensive view of Indigenous queer literature since Stonewall In The Queerness of Native American Literature, Lisa Tatonetti recovers ties between two simultaneous renaissances of the late twentieth century: queer literature and Native American literature. Throughout, she argues that queerness has been central to Native American literature for decades, showing how queer Native literature and Two-Spirit critiques challenge understandings of both Indigeneity and sexuality.
http://site.ebrary.com/id/11003362
Keywords: amérique du nord; amériques; approches et analyses; arts; autochtones; discipline; identités LGBTQIA2+; littérature; personnes bispirituelles; queer; ressource en ligne; régions géographiques; études littéraires